Evaluation of a Guidelines-Based Approach to the Treatment of Chronic Spontaneous Urticaria (2018)
ABSTRACT: Background: International scientific associations have made recommendations for the management of chronic spontaneous urticaria (CSU) that have been summarized in clinical guidelines. Objective: To evaluate the clinical impact of guideline recommendations for CSU management. Methods: A multicenter, triple-blinded, prospective, randomized study (the Urticaria Research of Tropical Impact and Control Assessment project; ClinicalTrials.gov identifier: NCT01940393) was performed. Patients older than 12 years and diagnosed with CSU were recruited and treated according to the European Academy of Allergy and Clinical Immunology/Global Allergy and Asthma European Network/European Dermatology Forum/World Allergy Organization guideline recommendations. The Dermatology Quality of Life Index (DLQI) was assessed every 2 weeks. As a first line of treatment, patients received a daily oral dose of antihistamine. After 4 weeks, in those patients without clinical response (DLQI ≤ 5), a higher dose (up to 4 times) of antihistamine was administered as a second line of therapy. After 2 months of follow-up, unresponsive patients received omalizumab or cyclosporine (as add-on therapy) for 4 months as a third line of treatment. Results: One hundred fifty patients were enrolled. After the first line of treatment, 88 patients (58.7%) reached a DLQI of 5 or less. With the second line of treatment, disease control rate was 76.7%. With the third line, 12 patients from the omalizumab group (8%) and 11 patients from the cyclosporine group (7.3%) reached a good clinical control (additional 15.3%). Control rate with line 1 treatment was superior at 1 month than at 2 weeks (P < .0001). Conclusions: The application of these guideline recommendations for CSU led to a high rate of disease control, assessed by scoring severity and patients' perception of quality of life. These results support the usefulness of guideline recommendations.